1H‐31P magnetic resonance spectroscopy: effect of biotin in multiple sclerosis. Issue 7 (27th June 2019) - Guillevin, Carole; Agius, Pierre; Naudin, Mathieu; Herpe, Guillaume; Ragot, Stéphanie; Maubeuge, Nicolas; Philippe Neau, Jean; Guillevin, Rémy
Abstract: Biotin is thought to improve functional impairment in progressive multiple sclerosis (MS) by upregulating bioenergetic metabolism. We enrolled 19 patients suffering from progressive MS (5 primary and 14 secondary Progressive‐MS). Using cerebral multinuclear magnetic resonance spectroscopy (MMRS) and clinical evaluation before and after 6 months of biotin cure, we showed significant modifications of: PME/PDE, ATP, and lactate resonances; an improvement of EDSS Neuroscore. Our results are consistent with metabolic pathways concerned with biotin action and could suggest the usefulness of MMRS for monitoring.